Role of thermally oxidized edible oils on metabolic functions and its implications in cardiovascular diseases - Sruthi, P K (Amala Cancer Research Centre, University of Calicut, 2025)
The growing prevalence of cardiovascular diseases (CVD) and metabolic disorders such as diabetes and obesity, has spurred extensive research into the dietary factors contributing to these conditions. Many studies have examined the impact of unhealthy fats, high-fat diets, or high-fat diets combined with high sugar, which are known to impair metabolic functions and raise the risk of metabolic disorders. In addition, thermally oxidized lipids as a class of deleterious molecules have been emerged as the cooking practice involves repeated heating of oils. Several studies have addressed the effect of oxidized and peroxidized lipids in the aetiology of many metabolic disorders. However, no studies have yet explored the effects of the consumption of thermally oxidized oils at a normolipidemic (5%) dietary level. This study aims to fill that gap by investigating the impact of long-term consumption of 5% thermally oxidized coconut oil, mustard oil, palm oil, and sunflower oil on carbohydrate and lipid metabolism in Wistar rats over six months. The rats were grouped into eight, with six animals per group and fed either unoxidized and thermally oxidized forms of these oils. Various parameters including physiochemical characterization of oils, body weight, carbohydrate metabolism, lipid metabolism and inflammatory markers related to cardiovascular disorders were assessed. Physico-chemical analysis revealed that oils rich in unsaturated fatty acids, especially sunflower oil, mustard oil and palm oil were more prone to oxidation, resulting in increased levels of carbonyl compounds, lipid oxidative products, and short-chain fatty acids. Conversely, coconut oil with its medium-chain fatty acids showed higher resistance to oxidation. In this study, rats fed thermally oxidized palm and sunflower oils experienced reduced body weight gain, while those fed coconut and mustard oils did not. Coconut oil, whether oxidized or not, enhanced insulin sensitivity, whereas oxidized mustard and palm oils led to hyperinsulinemia, dyslipidaemia and liver dysfunction. Thermally oxidized oils, particularly sunflower and palm oil promote hepatic steatosis, inflammation and elevated riskfactors for cardiovascular diseases. In conclusion, prolonged consumption of thermally oxidized oil, especially sunflower and palm oil even at normal dietary levels, significantly increases the risk of metabolic disorders such as insulin resistance, obesity, non-alcoholic fatty liver, and cardiovascular diseases. Although thermally oxidized coconut oil appears to be less harmful, it still poses some inflammatory risks. These findings underscore the health risks associated with the consumption of thermally oxidized oils, even at normal dietary levels.
Keywords: thermally oxidized oils; lipid oxidation products; metabolic disorders; cardiovascular disorder; coconut oil; palm oil; mustard oil; sunflower oil